Signals for reduced cognitive function are associated with subtle signs of atrial cardiomyopathy and left ventricular diastolic dysfunction – insights from a large population based study. (3rd October 2022) - Camen, S; Nagel, L; Bei Der Kellen, R; Barow, E; Schneider, J N; Blankenberg, S; Kirchhof, P; Wenzel, J P; Thomalla, G; Schnabel, R B
Abstract: Background/Introduction: In recent years, it has been proposed that a thrombogenic atrial substrate due to various alterations in (left) atrial morphology and function could contribute to atrial thromboembolism even in the absence of (clinically overt) atrial fibrillation. This so-called atrial cardiomyopathy may pose a risk of stroke and cognitive decline beyond the presence of atrial fibrillation. Purpose: To define the association of echocardiographic parameters of left atrial cardiomyopathy and left ventricular diastolic dysfunction with cognitive function in individuals free of clinically overt atrial fibrillation or stroke. Methods: Data from the first 10, 000 participants of a large German population-based cohort study were analysed. Of these, 8264 individuals underwent standardized transthoracic echocardiography and cognitive function testing at baseline. Parameters of left ventricular systolic and diastolic function as well as left atrial function were systematically assessed, including left atrial global peak strain. Cognitive function was quantified using the Animal Naming Test and the Trail Making Test A and B. We performed linear regression analyses with incremental adjustment to examine the association of echocardiographic parameters with the performance on the neuropsychological tests. Results: After exclusion of 463 individuals with known AF and 309 individuals with prior/known stroke or severe depression, 7492 individuals were analysed (mean age 61.9±8.4 years, 52.3% women, median left ventricular ejection fraction 59% [25th/75th percentile 56/62%], median left atrial volume index 25.0 ml/m 2 [25th/75th percentile 20/30 ml/m 2 ]). In multivariable-adjusted analyses, E/e'-ratio was significantly associated with a worse performance on the Animal Naming Test (−0.24 per one standard deviation [SD] increase, 95% confidence interval [CI] −0.42 to −0.06), the Trail Making Test A (0.76 per one SD increase, 95% CI 0.35–1.17) and B (1.1 per one SD increase, 95% CI 0.09–2.11). Left atrial strain was associated with worse performance on Trail Making Test B (−1.39 per one SD increase, 95% CI −2.46 to −0.32). Increased left atrial volume index was associated with worse performance on the ANT (0.2, 95% CI 0.03–0.37). Conclusions: Subtle echocardiographic signs of atrial cardiomyopathy and left ventricular diastolic dysfunction are associated with worse performance on cognitive function tests in a German middle-aged population. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): The Hamburg City Health Study (HCHS) is supported by the University Medical Center Hamburg-Eppendorf and by various grants from different institutions/organizations.